Positive impact of speech therapy in progressive non-fluent aphasia (2015)
The aim of this paper is to analyze the effects of intensive speech therapy intervention in a case of progressive non-fluent aphasia (PNFA). This is a dementia syndrome characterized by a progressive deficit in expressive language fluency and syntactic analysis, and by agrammatism and phonemic paraphasias. Although in the early stages there are no alterations in memory, comprehension, or visual processing, personality changes can slightly occur. To analyze the effects of speech therapy in this syndrome, a single case design with pre- and post-test was used. The participant was a male patient of 84 years with PNFA, who for twelve months received weekly speech therapy to stimulate the phonological, lexical and syntactic processing. He underwent neuropsychological assessment in three stages: six months before the onset of therapy, six months after therapy started and after completing 12 months of intervention. Assessment involved linguistic processing, general cognition, neuropsychiatric symptoms, quality of life (QOL) and activities of daily living (ADL). As a result of therapy, the patient showed a slight improvement in language prosody, fluency, and content of spontaneous speech, and a significant improvement in repetition, reading aloud, and oral-phonatory praxis. Other aspects of cognitive functioning (orientation, verbal naming, praxis, and memory) remained stable; ADLs and QOL improved. It is concluded that prolonged speech therapy can improve language processing and have a positive impact on other cognitive and socio-emotional processes in PNFA. This 12-month therapeutic stimulation not only slowed cognitive decline, but allowed to see maintenance of achievements and improvement of symptoms, which can be regarded as a success in PNFA treatment, considering the rapid progression of the disease.